2014
DOI: 10.5372/1905-7415.0802.279
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of Russell’s viper (Daboia siamensis) venom on renal tubular handling of sodium in isolated rabbit kidney

Abstract: Background:The common complication in cases of poisoning by Russell's viper (Daboia siamensis) venom (RVV) is acute renal failure, but the pathogenesis involved in the alteration of kidney function is still not well understood. Objective: To clarify the role of RVV in the pathogenesis of renal damage, the present study examines the functional short-term alterations acutely induced by RVV in isolated perfused rabbit kidney. Methods: Effects of RVV on renal tubular handling of sodium including mean perfusion pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 17 publications
3
16
0
Order By: Relevance
“…In the kidneys, the presence of hyaline cast was seen in renal tubules after 3 h venom administration. Similar renal morphologic changes have also been found in tissues exposed to the venoms of some Russell’s vipers, Micrurus species and other terrestrial elapids [ 25 , 30 32 ].…”
Section: Discussionsupporting
confidence: 59%
“…In the kidneys, the presence of hyaline cast was seen in renal tubules after 3 h venom administration. Similar renal morphologic changes have also been found in tissues exposed to the venoms of some Russell’s vipers, Micrurus species and other terrestrial elapids [ 25 , 30 32 ].…”
Section: Discussionsupporting
confidence: 59%
“…Preparation of the rabbit IPK was based on the previously described method ( Chaiyabutr et al, 2014 ). Briefly, adult male white New Zealand rabbits were fasted 24 h before the experiment with access to water ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…RVV group: The rabbit IPK was treated with 1 ml of the lyophilized RVV in normal saline (1 mg/ml), added into 100 ml of perfusate of the recirculating system after the 30-min equilibration period as an internal control. This dose was arbitrarily chosen on the basis of an earlier investigation in experimental animals in either dogs or rabbits, where the dosage of crude RVV that caused death in 50% of subjects (LD 50 ) by intravenously injection was 0.5 mg/kg body weight (BW) ( Chaiyabutr et al, 2014 , Tungthanathanich et al, 1986 ). This dosage was equivalent to a concentration of 10 μg/ml plasma, based upon an estimated plasma volume of 5% of the BW.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggested that the renal tubular loss of electrolytes including sodium, potassium and magnesium might be caused by the direct toxicity of snake venom from the Viperidae family. A previous experimental study of Russell's viper venom demonstrated decreased renal tubular absorption of sodium in proximal and distal renal tubules resulting in increased fractional excretion of sodium due to Na + −K + −ATPase activity inhibition of renal tubules in both the renal cortex and medulla [34] .…”
Section: Resultsmentioning
confidence: 99%